2015
DOI: 10.1007/s00259-015-2996-7
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglial component complicates the prediction of tumour grading with metabolic imaging

Abstract: For better characterization of gliomas and for risk assessment, the results of metabolic PET imaging should be revised after obtaining the pathological report, because oligodendroglial differentiation may positively influence the substrate metabolism and thus complicated the preoperative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
5
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 20 publications
2
24
5
3
Order By: Relevance
“…Previous studies evaluating the DTA of MET PET to discriminate between LGG and HGG have shown inferior results when including oligodendroglial tumours. 41 While our study contradicts these results, the explanation can be our adherence to the WHO 2016 guidelines 1 by excluding oligoastrocytomas. Excluding oligoastrocytomas in the analysis yielded a similar AUC for the discrimination between LGG and HGG in astrocytomas and oligodendrogliomas respectively.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies evaluating the DTA of MET PET to discriminate between LGG and HGG have shown inferior results when including oligodendroglial tumours. 41 While our study contradicts these results, the explanation can be our adherence to the WHO 2016 guidelines 1 by excluding oligoastrocytomas. Excluding oligoastrocytomas in the analysis yielded a similar AUC for the discrimination between LGG and HGG in astrocytomas and oligodendrogliomas respectively.…”
Section: Discussioncontrasting
confidence: 78%
“…24,27 Many researchers tried to address this issue using imaging markers derived from positron emission tomography, with conflicting results. [28][29][30] Interestingly, the difference between the pure astrocytoma and oligodendroglioma group was significant neither for grade II nor for grade III in this study. This might be due to the lack of robustness of iVASO or the relatively small sample in this cohort.…”
Section: Discussioncontrasting
confidence: 73%
“…It was reported that oligodendroglioma showed higher perfusion than pure astrocytoma, which might confound the reliability of perfusion metrics in predicting tumor grade and clinical outcomes . Many researchers tried to address this issue using imaging markers derived from positron emission tomography, with conflicting results . Interestingly, the difference between the pure astrocytoma and oligodendroglioma group was significant neither for grade II nor for grade III in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…18.11. It is well [45,46], and that MET is good at showing the tumor boundary. The FDG uptake increases with the tumor grade [47], and the results here suggest that FMISO uptake is absent in grades II and III, but strong in grade IV.…”
Section: Discussionmentioning
confidence: 91%